Achaemenid Period Ceramic Typology from the Ramhormoz Plain in Southwest Iran: Eastern Anatolia, Southern Mesopotamia Relations - Leila Afshari; Soraya Afshari; Behrouz Omrani (Anadolu Araştırmaları)
The Ramhormoz Plain and large portions of its northern piedmont are part of modern-day Khuzestan province. A season-long survey was conducted in this region in 2020. During this survey, cultural artifacts were identified and recorded at 36 sites from the Achaemenid period. This identification was based on the pottery seen on the surface. The identification of Achaemenid settlements in the Ramhormoz plain was made possible by taking into account the local pottery of Khuzistan reported from the Tappeh Darough. This study both describes the types of pottery from the Achaemenid period as well as introduces various settlements of this period. Two of the most diagnostic vessel forms of the Achaemenid period in the Ramhormoz collection are carinated bowls and jars with everted rims. Most of the pottery discovered is local, but the overall study of the Achaemenid pottery of the Ramhormoz Plain shows the limited influence of the pottery tradition of the Persians and of northwestern Iran. Pottery traditions of eastern Anatolia and southern Mesopotamia can only be identified to a limited extent in the Ramhormoz Plain.